Akibat Sindrom Burnout Terhadap Kinerja Pekerjaan - Indah Rahmawati Putri; Ageng S. Kanda (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Humans play an active role in every organizational activity, because humans are planners, actors and determinants of the realization of organizational goals. Goals cannot be realized without the active role of employees. Managing employees is difficult and complex, because they have thoughts, feelings, status, desires and backgrounds outside the organization. Employees cannot be managed and controlled completely like managing machines, capital or warehouses. Labor is a very important asset. Humans are a workforce for organizations who are sometimes often overlooked as valuable assets. Not infrequently, an office only considers labor (employees) as a burden that must always be reduced to reduce work costs. However, that is an inaccurate view. Employees are the only asset that cannot be duplicated and copied by other humans because in essence each person is a unique creature created by a supreme creator with different characteristics. Therefore, the workforce must always be maintained and developed so that it provides maximum output for the office in general. In an organization, always reminding each employee to excel in achieving goals. An organization's work is influenced by many factors, one of which can influence performance is if Employees are able to face difficulties both inside and outside of work.